2020
DOI: 10.1002/ptr.6898
|View full text |Cite
|
Sign up to set email alerts
|

The common diabetes drug metformin can diminish the action of citral against Rhabdomyosarcoma cells in vitro

Abstract: Rhabdomyosarcoma (RMS) is a rare type of soft tissue sarcoma most commonly found in pediatric patients. Despite progress, new and improved drug regimens are needed to increase survival rates. Citral, a natural product plant oil can induce cell death in cancer cells. Another compound, metformin, isolated originally from French lilac and used by diabetics, has been shown to reduce the incidence of cancer in these patients. Application of citral to RMS cells showed increase in cell death, and RD and RH30 cells sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, metformin was able to decrease the citral-induced antinociceptive action during the phase two of the formalin test (Figure 4). This last result comes to an agreement with the ability of metformin to block the action of citral against rhabdomyosarcoma cells in vitro (Duan et al 2021).…”
Section: R a F Tsupporting
confidence: 83%
“…However, metformin was able to decrease the citral-induced antinociceptive action during the phase two of the formalin test (Figure 4). This last result comes to an agreement with the ability of metformin to block the action of citral against rhabdomyosarcoma cells in vitro (Duan et al 2021).…”
Section: R a F Tsupporting
confidence: 83%
“… Zhang et al (2017) revealed that treatment with metformin increased VDAC expression and decreased superoxide dismutase 1 (SOD1) in PCOS-like rats compared to control rats ( Zhang et al, 2017 ). In addition, metformin in the presence of citral, but not in its absence, increased VDAC expression ( Duan et al, 2021 ). Moreover, VDAC1 is overexpressed in diseases that were found to be modulated by metformin ( Table 1 ).…”
Section: Voltage-dependent Anion Channel: Isoforms Mitochondria Function and Overexpressionmentioning
confidence: 99%
“…Moreover, in the cortical region, plasmalemmal VDAC1 (pl-VDAC1) was found as oligomers in areas where metformin induced Aβ-aggregate accumulation, and apoptotic neurons were observed ( Wijesekara et al, 2017 ). In addition, metformin increased VDAC1 expression levels in NCaP cells ( Loubiere et al, 2017 ) and in polycystic ovary syndrome-like rats ( Zhang et al, 2017 ), and in the presence of citral ( Duan et al, 2021 ).…”
Section: Metformin Mode Of Actionmentioning
confidence: 99%
See 2 more Smart Citations